Long-term oral administration of Paederia foetida decreases cytochrome P450 mRNA expression: The predictive approaches in a rat model - Phisit Pouyfung, Saruda Kuraeiad, Supabhorn Yimthiang, Tanaporn Khamphaya (Journal of Applied Pharmaceutical Science, 2023)
Paederia foetida (Linn.) is one of the medicinal plants containing various bioactive compounds (e.g., beta-sitosterol and ursolic acid), which has been widely used in medicine and cuisine among different communities. It exhibits several pharmacological properties, including anti-inflammatory, antioxidant, antidiabetic, and anticancer. However, its toxicity on the liver and kidney, as well as its effect on hepatic drug-metabolizing enzymes, lacks documentation. Therefore, the toxic effects of P. foetida on the liver and kidney and metabolizing enzymes were explored. In a recent study, male Wistar rats were grouped into five groups and gavaged daily with 0–1,000 mg/kg BW of a P. foetida extract (PFE) for 8 weeks. After euthanasia, liver, kidney, and blood samples were collected and subjected to histological and biochemical analysis. The important cytochrome P450 mainly expressed in the rat liver, including Cyp3a1, Cyp2d1, and Cyp2c6, was investigated. There were no changes in body and organ weight between groups. However, the liver weight of rats treated with 1,000 mg/kg BW PFE was increased when compared to the control group. The liver and kidney histopathology were observed with no difference between groups. The markers of liver damage (alanine aminotransferase and aspartate aminotransferase) and kidney damage (blood urea nitrogen and creatinine) between all groups showed no change. Cyp3a1, Cyp2d1, and Cyp2c6 mRNA expression levels among PFE-treated groups were decreased in a dose-dependent manner, suggesting that subchronic exposure to this extract significantly reduces Cyp3a1, Cyp2d1, and Cyp2c6 expressions in rat livers without toxicity or change in histology and biochemical data. However, its concomitant use with prescription drugs needs further investigation.
Keywords: Cytochrome p450 expression, Cyp3a1, Cyp2d1, Cyp2c6, Paederia foetida, liver toxicity, kidney toxicity